Inventory Analysis To Get Profit PT. Agri First Indonesia - Hendra Saputra; Ayu Kurnia Sari; Jonathan Pakpahan (Yayasan Multidimensi Kreatif, 2024)
In the era of recent globalization, inventory is one of the most active and important elements of assets in the company's operating process, which is obtained to be produced into finished goods and then sold, marketed or goods to be used. Therefore, the description and measurement of inventory must be carried out carefully and clearly. Inventory is particularly important because this item can materially affect both the profit and loss calculation and the statement of financial position within a company. The term inventory indicates goods owned by the company used for the normal activities of the company. Both those used for resale and those that are reused or used for the production process. The results of the study state that the recording method used in the company PT Agri First Indonesia is a perpetual system that allows inventory information to be known at any time and this is very helpful to management because the company is engaged in retail trade whose inventory turnover is quite high so that with this perpetual method, anticipation can be made so that there are no shortages and excess inventory. This is in accordance with PSAK No. 14. Because the company always records every transaction into the transaction account so that at any time the amount of inventory can be known. However, this system has a weakness, namely that current costs are not compared with future revenues.